Iodine Supplementation in Mildly Iodine-Deficient Pregnant Women Does Not Improve Maternal Thyroid Function or Child Development: A Secondary Analysis of a Randomized Controlled Trial - Verhagen, Nicole J. E.; Gowachirapant, Sueppong; Winichagoon, Pattanee; Andersson, Maria; Melse-Boonstra, Alida; Zimmermann, Michael B. (Frontiers in Endocrinology, 2020)
Background Iodine deficiency during pregnancy may be associated with lower offspring IQ, but there are few data on the safety and efficacy of maternal iodine supplementation on child development. In a previously reported multi-center randomized trial conducted in Thailand and India, we assessed the effect of iodine supplementation in mildly iodine-deficient pregnant women on offspring development. In this secondary analysis of that trial, we report data only from the Thai pregnant women in the study, who were more iodine deficient at entry. Methods Pregnant women in Bangkok, Thailand, were randomized to receive daily 200 µg oral iodine or placebo until delivery. We assessed thyroid size and thyroid function during pregnancy and cognitive and motor development at ages 1, 2 and 5.7 years. The trial was registered at www.clinicaltrials.gov/NCT00791466. Findings Women (n=514) entered the trial between November 2008 and March 2011 at a mean ± SD gestational age of 11 ± 2.8 weeks; their median (IQR) UIC was 112 (75, 170) µg/L. Mean compliance with supplementation was 88%. We assessed 397 mothers in the 3rd trimester, 231 infants at age 2 y and 157 children at mean age 5.7 y. During pregnancy, there was a slightly greater decrease in free and total thyroxine concentrations in the iodine group (p<0.05). At age 2 years, the iodine group had borderline lower scores for combined fine and gross motor function (p=0.05), but there were no other significant differences in development. At 5.7 years, there were no significant group differences in child development. Conclusion Daily iodine supplementation in mildly iodine deficient pregnant women was associated with small negative effects on maternal thyroxine concentrations, but did not affect child development. The safety and efficacy of iodine supplementation in mildly-iodine deficient pregnant women needs to be evaluated further in large randomized controlled trials.